ANALYSIS OF THE CAUSES OF NARCOTICS RECIDIVITIES IN CLASS IIA PRISONS IN BOGOR - Septiawan, Yudha Nugraha (Walisongo Law Review (Walrev), 2020)
The risk can cause harm to someone, including people who have used narcotics. Drug abuse is a concern for many people today. Misuse of narcotics is a deviation of behavior or deeds that violate the law, and it is unfortunate if prisoners who are free to repeat the narcotics crime again. The problem that became the reference in this research is whether the factors that cause the repetition of narcotics crime, how the risk of repetition of narcotics crime, and how to overcome the narcotics crime repetition. The purpose of this study is to determine the factors, risks, and efforts in overcoming repetition of narcotics crime. This research was conducted using a qualitative approach by collecting data using interview, observation, and documentation methods. Data analysis is described in the form of sentence descriptions and analyzed qualitatively, then a conclusion is drawn. Based on the results of research and discussion, it is concluded: (1) Factors that influence the repetition of narcotics crime are internal factors and external factors. (2) The risk of repetition of narcotics crime is carried out in the level of risk classification. (3) Efforts to overcome the repetition of narcotics crime shall be carried out in a preventive and repressive manner. The advice given is maximizing rehabilitation activities carried out in Corrections Institutions and maximizing coaching programs in Corrections Institutions